Magnetic resonance imaging findings of knee injury - Hussein, Dhafer L.; AL-Iasghar, Abdullateef; AL-Hillim., Mohammed (AL-Kindy College Medical Journal, 2015)
Background: Since its introduction to musculoskeletal imaging in the early 1980, magnetic resonance imaging (MRI) has revolutionized diagnostic imaging of the knee. It is therefore become the examination of choice in the evaluation of internal joint structures of the knee like menisci, cruciate ligaments, and articular cartilage.Objectives: to describe the MRI finding in various knee injuries.Patients and methods: A cross sectional study was done on 130 patients with history of knee injury in MRI unit at institute of radiology and al-Shaheed Ghazi Al-Hariri Hospital in medical city complex - Baghdad, from October 2011 to February 2013 includes 103 men, 27 women; the mean age was 33.86 years. MR imaging studies of the knee performed using a 1.5 T MR system. The sequences included coronal and sagittal PD, sagittal T2 FSE, fat suppressed T2 FSE, STIR axial and coronal. Knee MR studies were obtained to evaluate ligament, menisci, articular surface and bone pathologies of knee injuries.Results: MR images were normal in 15 patients; it was positive for meniscal tears in 59 patients and maximum involvement was in the medial meniscus and the posteriorhorn. These tears were classified into grade 1 (28.8%), grade 2 (11.5%), grade 3 (53.9%) and grade 4 (5.8%). Ligament tears were seen in 70 patients. Secondary signs associated with ligament tears were also assessed.Conclusions: MRI is an accurate, non-invasive technique for examination of the soft tissues and osseous structures of the knee. It has great capability in diagnosing meniscal tears and classifying them into grades and types, which would avoid unnecessary arthroscopic examination. It is a very good modality to diagnose complete tears of the anterior cruciate ligament (ACL).maging, meniscus